Quantum choas and rotational damping - Åberg, S. (Progress in Particle and Nuclear Physics, 1992)
The appearence of quantum chaos in the excited rapidly rotating nucleus is studied in a simple nuclear model, consisting of the cranked Nilsson model with a schematic two-body interaction added. Chaos is found to smoothly set in at a much lower excitation energy in normal-deformed 168Yb than in superdeformed 152Dy. A dynamical sign of chaos is a saturation of the standard deviation of the E2-strength function, and also the disapearence of correlations in γ-γ-correlations. Motional narrowing may however restore the correlations also for the completely chaotic case. The distribution of E2-matrix elements strongly deviate from Porter-Thomas result, and many more strong γ-transitions appear than expected from GOE-theory. Transition entropy is introduced as a measure of order in the E2 cascade.
Keywords: GOE-analyses; high spin; motional narrowing; Quantum chaos; rotational damping; superdeformation; transition entropy; γ-γ-correlations